PENANGANAN DAN PENGAWASAN PERPAJAKAN DALAM RANGKA INTENSIFIKASI DI BIDANG E-COMMERCE (STUDI PADA KANTOR PELAYANAN PAJAK PRATAMA MALANG SELATAN) - Aprilia, Anita (Jurnal Mahasiswa Perpajakan, 2014)
The globalization era has very board impact on the development of human activities, including business and trade. The correct development in trading activity is the use of electronic media for sellers to offer products and for buyers to purchase them. This phenomenon is called as e-commerce. This study to describe and analyse the efforts of Taxation Office in Malang (Kantor Pelayanan Pajak Pratama Malang Selatan) in handling and supervising e-commerce taxation. ThisÂ  study found that Directorat General of Taxation (Direktorat Jenderal Pajak) has classified several models of e-commerce, that helps the officers to manage the taxation aspect. This study also found some such as the low compliance level of difficulties tax payers to report their activities and the lack of supporting taxation system and regulationon e-commerce. Keywords: e-commerce, handling and supervision, taxation.